2011
DOI: 10.1097/qad.0b013e32834babb3
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis delta in HIV-infected individuals in Europe

Abstract: The prevalence of anti-HDV in chronic HBsAg-positive/HIV carriers in EuroSIDA is 14.5%. Most of these patients exhibit detectable HDV viraemia. Viral interference between HBV and HDV is manifested in all but HBV genotype D carriers in whom overt coreplication of both viruses occurs which might result in enhanced liver damage. Overall, delta hepatitis increases the risk of liver-related deaths and overall mortality in HIV patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 31 publications
8
78
2
Order By: Relevance
“…In our study, 14% of positive HDV screening tests were false-positive. After the exclusion of these patients, 63% of HDVpositive patients had a detectable HDV viral load, which was lower than the proportion found in the EuroSIDA study 4 . Although the main reason for this difference remains unclear, the unselected nature of our study population, in which all patients were screened for HBV and HDV infection independently of clinical manifestations or laboratory abnormalities, might have played an important role.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In our study, 14% of positive HDV screening tests were false-positive. After the exclusion of these patients, 63% of HDVpositive patients had a detectable HDV viral load, which was lower than the proportion found in the EuroSIDA study 4 . Although the main reason for this difference remains unclear, the unselected nature of our study population, in which all patients were screened for HBV and HDV infection independently of clinical manifestations or laboratory abnormalities, might have played an important role.…”
Section: Discussioncontrasting
confidence: 65%
“…Of a selected sample of 422 hepatitis B surface antigen (HBsAg) carriers in the EuroSIDA collaboration, 61 (14%) were coinfected with HDV 4 . The prevalence of anti-HDV antibodies seems even higher in HIV/HBV-coinfected patients from SSA, reaching 25% in GuineaBissau 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Also other studies in Africa have showed varying prevalence rates of HDV ranging from 0-50% in different countries [18][19][20] . Similarly in the developed countries, high anti-HDV prevalence's of 10-15% have been documented in recent studies 1,21,22 . Reasons for the variations in the prevalence of HDV exposure or infection are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for the variations in the prevalence of HDV exposure or infection are not clear. This could be a result of modes of transmission whereby in some of these countries there could be higher rates of IVD use 21,22 . In addition, we have confirmed earlier findings that male gender was significantly associated with anti HDV antibody positivity 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…HBV reactivation is more likely to occur in HIV patients even after HBs antibody response (1,8). Hepatitis delta virus (HDV) represents a risk factor for the severity of chronic hepatitis B, but was not associated with progression to the stage of acquired immunodeficiency syndrome (AIDS) (9).…”
Section: Introductionmentioning
confidence: 99%